Pengaruh Kemampuan Teknik Personal Pada Efektivitas Penggunaan SIA Dengan Budaya Organisasi Sebagai Variabel Pemoderasi - Suputeri, I Gusti Ayu; Suardikha, I Made Sadha (E-Jurnal Akuntansi; Vol 26 No 2 (2019)DO - 10.24843/EJA.2019.v26.i02.p07, 2019)
The purpose of this study was to determine the effect of personal technical abilities on the effectiveness of the use of accounting information systems with organizational culture as moderating variables. The population in this study was 19 hospitals in the city of Denpasar and research samples were taken using non probability sampling. Respondents in this study amounted to 131 employees. Data collection is done by distributing questionnaires. The data analysis technique used is the analysis of Moderated Regression Analysis (MRA). The results of this study indicate that the personal technique ability variable has a positive effect on the effectiveness of the use of accounting information systems and organizational culture variables able to strengthen the influence of personal technical skills on the effectiveness of the use of accounting information systems. Keywords : personal technical skills, SIA